Application of ANOVA and Taguchi Methods for Evaluation of the Surface Roughness of Stellite-6 Coating Material - Ozturk, Sabri (CARL HANSER VERLAG, 2014)
In this study, the machinability of Stellite-6 coating was examined using a ceramic cutting tool. Orthogonal tube-cutting experiments were performed on a lathe and the data collected was evaluated by analysis of variance (ANOVA) to find out the percentage contributions of the key factors. Whisker reinforced ceramic inserts with ISO tool designations RNGN 1907 00T01020 were used for the machining trials and round type cutting tool inserts which are common in the manufacturing industry were chosen. Taguchi design of experiments was implemented to determine the optimal cutting parameters for analyzing the effects of the cutting speed and feed rate on the surface quality. Four cutting speeds and three feed rates were used during the turning operations to produce the regression model for Ra (average surface roughness) in terms of the actual parameter values. Hardness of the cutting inserts gets affected significantly at higher feed rate.
Keywords: Materials testing; ceramic cutting tool; Stellite-6; analysis of variance (ANOVA); feed rate; CUTTING TOOLS; CERAMIC TOOLS; WEAR; MODEL; PERFORMANCE; PREDICTION; FINISH; LIFE; Materials Science